Data Management with Risk Management in Engineering and Science Projects - Vieira, R. J. C. (2014)
Engineering and Science projects are facing new data management challenges, which are currently being addressed through the development of data management plans. However, project stakeholders are unable to proper assess if their plan is representative of good data management practices. To address this issue, we propose a risk management framework to assist the definition of a data management plan in engineering and science projects. To validate our proposal, we present an application to a civil engineering project concerning dam safety.